2016
DOI: 10.1089/jmf.2015.3557
|View full text |Cite
|
Sign up to set email alerts
|

Relative Inhibitions of 5-Lipoxygenase and Myeloperoxidase and Free-Radical Scavenging Activities of Daidzein, Dihydrodaidzein, and Equol

Abstract: The effects of bioavailability and metabolic transformation on the biological activities of daidzein are relatively unknown. The effects of daidzein, dihydrodaidzein, and equol at physiologically relevant concentrations on the production of leukotriene B4 and F2-isoprostanes, and myeloperoxidase enzyme activity in freshly isolated human neutrophils were examined. Equol, at physiological concentrations, inhibited leukotriene B4 production (IC50-200 nmol/L) in human neutrophils significantly more than daidzein a… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
6
0

Year Published

2017
2017
2024
2024

Publication Types

Select...
8
1

Relationship

1
8

Authors

Journals

citations
Cited by 12 publications
(6 citation statements)
references
References 35 publications
0
6
0
Order By: Relevance
“…None of the studies included in Table S1 tested whether the phenolic compounds target LT receptors (i.e., BLT1 and BLT2), FLAP, and/or LTC 4 hydrolase. Regarding LTA 4 hydrolase, only one study showed that isoflavones failed to inhibit (or promote) its enzymatic activity [ 143 ]. Thus, the characterization of the interaction of phenolic compounds with these elements will be essential in future studies.…”
Section: Resultsmentioning
confidence: 99%
“…None of the studies included in Table S1 tested whether the phenolic compounds target LT receptors (i.e., BLT1 and BLT2), FLAP, and/or LTC 4 hydrolase. Regarding LTA 4 hydrolase, only one study showed that isoflavones failed to inhibit (or promote) its enzymatic activity [ 143 ]. Thus, the characterization of the interaction of phenolic compounds with these elements will be essential in future studies.…”
Section: Resultsmentioning
confidence: 99%
“…While research on the anti-inflammatory effects of genistein has been cumulative, few studies have reported about the effect of equol on inflammation, but some physiological effects of equol such as antioxidant activity are stronger than that of genistein and daidzein (Setchell et al 2002b). Recently, Tsen et al (2016) reported that equol inhibited LTB 4 production in human neutrophils, and the activity was significantly higher than that of daidzein, suggesting the effect may be due to the inhibition of 5-LOX. Here, we showed that equol might also be a potent inhibitor of LTB 4 production by mast cells, with activity that is stronger than that of daidzein and genistein.…”
Section: Discussionmentioning
confidence: 99%
“…The cellular anti-inflammatory capacity of the apple beverage was determined by measuring the inhibition of LTB4 production and MPO activity of freshly isolated human neutrophils. Human neutrophils were isolated from the neutrophil/ erythrocyte pellet of fresh human whole blood after Ficoll-Paque gradient centrifugation and dextran sedimentation of red blood cells (Tsen et al, 2016). The whole human blood was obtained in kind from the study researchers, as such human ethics approval is not required.…”
Section: Antioxidant and Anti-inflammatory Capacitymentioning
confidence: 99%